1907 Ala. Laws 80 - (:unkn) unknown (General Publisher, 1907)
Prohibiting selling or bartering any pistol of less than twenty-four inches in length of barrel or any brass knucks, metalic knucks, dirks, slungshot, Bowie knives, or knife of like kind. Violators fined not less than one hundred nor more than one thousand dollars, and perhaps also sentenced to hard labor not less than one nor more than than three months.
--
Keywords: TRANSFER